2010
DOI: 10.1007/s00296-010-1698-5
|View full text |Cite
|
Sign up to set email alerts
|

Synovial/Serum leptin ratio in rheumatoid arthritis: the association with activity and erosion

Abstract: Reports suggest leptin, which was initially described as a hormone that regulates food intake and energy balance, has an intimate relationship, and interacts with the immune system. Leptin consumption in the synovial cavity in patients with rheumatoid arthritis (RA) reported to have protective effect against erosion. To determine the difference in serum leptin and synovial/serum leptin ratio between RA and control and to assess whether these parameters correlate with systemic inflammation in RA. Also, the hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 26 publications
(46 reference statements)
2
63
0
3
Order By: Relevance
“…Serum leptin, synovial leptin and the synovial/serum leptin ratio in RA patients were found to be significantly higher than in control subjects. Interestingly, serum leptin in RA patients with effusion was higher than the matched synovial leptin [23], suggesting that local consumption of leptin in the joint cavity could protect against the destructive course of RA. Figenschau et al [104] showed increased proliferation and an enhanced synthesis of extracellular matrix by leptin-induced chondrocytes.…”
Section: Proinflammatory and Anti-inflammatory Effects Of Leptin On Ramentioning
confidence: 95%
See 1 more Smart Citation
“…Serum leptin, synovial leptin and the synovial/serum leptin ratio in RA patients were found to be significantly higher than in control subjects. Interestingly, serum leptin in RA patients with effusion was higher than the matched synovial leptin [23], suggesting that local consumption of leptin in the joint cavity could protect against the destructive course of RA. Figenschau et al [104] showed increased proliferation and an enhanced synthesis of extracellular matrix by leptin-induced chondrocytes.…”
Section: Proinflammatory and Anti-inflammatory Effects Of Leptin On Ramentioning
confidence: 95%
“…In short, there are several potential explanations for these differing results among these studies: first, the relatively small sample size may not precisely represent the larger patients; secondly, the baseline characteristics such as disease duration, age, race and BMI can be inconsistent, which may affect the expression level of leptin; thirdly, patients with other co-existing autoimmune diseases cannot be excluded from studies, which could be potential confounding factors; and fourthly, different measurement methods of leptin levels, such as radioimmunoassay [20,37,40,100] and enzyme-linked immunosorbent assay (ELISA), may also cause deviation [8,23,30]. In addition, discrepancies in leptin levels in RA patients could be due to different treatments that intervene with the endocrine system, which usually complicates human experimental researches.…”
Section: Leptin Levels In Serum Synovial Fluid and Synovial Tissue Amentioning
confidence: 99%
“…Experimental studies on mice demonstrated that these animals showed less severe stages of induced RA with lower levels of IL-1B and TNF-α in the synovial fluid and reduction in T-cell proliferative response induced by antigen [14]. However, clinical studies revealed paradoxical results about the effects of endogenous leptin in protecting joints in severe forms of erosive RA in humans [15].…”
Section: Leptinmentioning
confidence: 99%
“…[17] Thus, leptin levels may be a risk factor for the pathogenesis of RA [18]. Olama et al (2012) [15] evaluated the ratio of synovial and serum leptin in patients with RA and found that the local utilization of leptin at the joint cavity has a Records identified through database searching (n = 38)…”
Section: Leptinmentioning
confidence: 99%
“…Several authors have demonstrated a dependence between the risk of aggressive course of RA and leptin levels (Kadowaki & Yamauchi, 2005;Lee et al, 2007;Targonska-Stepniak et al, 2008;Whitehead et al, 2006). It is widely accepted that leptin levels are elevated in patients with RA and that there is a correlation between serum leptin and synovial fluid/serum leptin ratio and disease duration and parameters of RA activity (Olama et al, 2010). Generally, leptin is considered to be pro-inflammatory, but this hormone has been also reported to reduce radiographic joint damage (Rho et al, 2009).…”
Section: Leptinmentioning
confidence: 99%